Manobalai Nature Reserve : plan of management - New South Wales. Department of Environment, Climate Change and Water. Parks and Wildlife Group; New South Wales. National Parks and Wildlife Service ([Sydney] : DECCW, 2010)
"Manobalai Nature Reserve is located near the small township of Sandy Hollow, approximately 30 kilometres west of Muswellbrook and approximately 200 kilometres North-West of Sydney."--P. 1.
"May 2010".
"DECCW 2010/496"--Verso t.p.
"This plan of management was adopted by the Minister for Climate Change and the Environment on 18th May 2010."--Verso t.p.
"This plan of management is based on a draft plan prepared by staff of the Central Coast Hunter Range Region of NPWS."--Verso t.p.
Includes bibliographical references (p. 14)
Also available online. On 3/11/2008 freely available from the website of DECCW at: http://www.environment.nsw.gov.au/resources/planmanagement/final/20100496ManobalaiNR.pdf
Keywords: Natural areas -- New South Wales -- Management; National parks and reserves -- New South Wales -- Management; Conservation of natural resources -- New South Wales; Manobalai Nature Reserve (N.S.W.) -- Management